Asymmetric Phenotypes of Sterile Hybrid Males From Reciprocal Crosses Between Species of the Anopheles gambiae Complex - Liang, Jiangtao; Hodge, James M.; Sharakhov, Igor V. (Frontiers in Ecology and Evolution, 2021)
Haldane’s rule of speciation states that sterility or inviability affects the heterogametic sex of inter-species hybrids. Darwin’s corollary to Haldane’s rule implies that there are asymmetric phenotypes in inter-species hybrids from reciprocal crosses. Studying the phenotypes of F1 hybrids among closely related species of malaria mosquitoes can assist researchers in identifying the genetic factors and molecular mechanisms of speciation. To characterize phenotypes of sterile hybrid males in the Anopheles gambiae complex, we performed crosses between laboratory strains of An. merus and either An. gambiae or An. coluzzii. The reproductive tracts had normal external morphology in hybrid males from crosses between female An. merus and male An. gambiae or An. coluzzii. Despite being sterile, these males could copulate with females for a normal period of time and could transfer a mating plug to induce female oviposition and monogamy. In contrast, the entire reproductive tracts in hybrid males from crosses between female An. gambiae or An. coluzzii and male An. merus were severely underdeveloped. These males had atrophic testes and reduced somatic organs of the reproductive system including male accessary glands and ejaculatory duct. In addition, hybrid males with underdeveloped reproductive tracts displayed a shorter copulation time with females and failed to induce female oviposition and monogamy due to their inability to form and transfer a plug to females during mating. The asymmetry of the phenotypes associated with hybrid male sterility suggests that different genetic factors and molecular mechanisms are responsible for reproductive isolation in reciprocal crosses among species of the An. gambiae complex.